Biofiltration of hydrogen sulphide using schist as packing material: biofilters performances and tortuosity assessment of the packed bed (2010)
In the present work it was tested the performance of schist, a volvanic rock, and the possible improving on mixing it with UP20. The experimental setup was the same used in previous works and the analysis included the biofilter removal capacity and physical parameters such as porosity, pressure drop, tortuosity and superficial area.